The identification and distribution of selected families of planktonic hyperiids (Crustacea, Amphipoda) in the Gulf of Thailand and the South China Sea - Rachanee Siriyong (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 1975